T-wave alternans poorly prognostic in primary prophylactic ICD patients: a prospective EU-CERT-ICD study. (3rd October 2022) - Pelli, A; Junttila, M J; Kentta, T V; Schlogl, S; Zabel, M; Malik, M; Reichlin, T; Willems, R; Vos, M A; Harden, M; Friede, T; Sticherling, C; et al.
Abstract: Background: New methods to identify patients who truly benefit from primary prophylactic implantable cardioverter defibrillation (ICD) are urgently needed. T-wave alternans (TWA) represents a beat-to-beat fluctuation in the morphology of the ST-segment and T-wave. It has been shown to associate with arrhythmogenesis of heart and sudden cardiac death [1]. We hypothised that TWA might associate with benefit from ICD implantation in primary prevention. Methods: In EU-CERT-ICD study, we prospectively enrolled 2327 primary prophylactic ICD candidates from 15 European countries. A 24-hours Holter-monitoring was taken from all recruited patients at enrolment. TWA was assessed from Holter-monitoring using MMA method with Getemed Cardioday software. To assess the benefit from ICD treatment, we used outcomes all-cause mortality, appropriate shock and survival benefit. We conducted Cox regression model, competing risk regression model and propensity score adjusted Cox regression model. TWA was assessed both as contiguous variable and with cut-off points <47 μV and <60 μV. Results: Final cohort included 1, 734 valid T-wave alternans samples, 1, 211 patients with ICD and 523 control patients with conservative treatment, with mean follow-up time 2.3 years. TWA <60 μV predicted lower all-cause mortality in ICD patients in univariate cox regression model (HR 1.484, 95% CI 1.024–2.151, p=0.0374). In multivariate models, TWA did not predict death or appropriate shocks in ICD patients. In addition, TWA did not predict death in control patients. In propensity score adjusted Cox regression model, TWA did not predict ICD benefit. Conclusion: T-wave alternans is poorly prognostic in primary prophylactic ICD patients. Altough it may predict life-threatening arrhythmias and sudden cardiac death in several patient populations, it cannot be used in assessing benefit from implantable cardioverter defibrillator in primary prevention among patients with ejection fraction ≤35%. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Community's 7th Framework Program FP7/2007-2013